Secondary organic aerosol origin in an urban environment: influence of biogenic and fuel combustion precursors. (27th April 2016) - Minguillón, M. C.; Pérez, N.; Marchand, N.; Bertrand, A.; Temime-Roussel, B.; Agrios, K.; Szidat, S.; van Drooge, B.; Sylvestre, A.; Alastuey, A.; Reche, C.; Ripoll, A.; et al.
Abstract : Source contributions of organic aerosol (OA) are still not fully understood, especially in terms of quantitative distinction between secondary OA formed from anthropogenic precursors vs. that formed from natural precursors. In order to investigate the OA origin, a field campaign was carried out in Barcelona in summer 2013, including two periods characterized by low and high traffic conditions. Volatile organic compound (VOC) concentrations were higher during the second period, especially aromatic hydrocarbons related to traffic emissions, which showed a marked daily cycle peaking during traffic rush hours, similarly to black carbon (BC) concentrations. Biogenic VOC (BVOC) concentrations showed only minor changes from the low to the high traffic period, and their intra-day variability was related to temperature and solar radiation cycles, although a decrease was observed for monoterpenes during the day. The organic carbon (OC) concentrations increased from the first to the second period, and the fraction of non-fossil OC as determined by 14 C analysis increased from 43% to 54% of the total OC. The combination of 14 C analysis and Aerosol Chemical Speciation Monitor (ACSM) OA source apportionment showed that the fossil OC was mainly secondary (>70%) except for the last sample, when the fossil secondary OC only represented 51% of the total fossil OC. The fraction of non-fossil secondary OC increased from 37% of total secondary OC for the first sample to 60% for the last sample. This enhanced formation of non-fossil secondary OA (SOA) could be attributed to the reaction of BVOC precursors with NOx emitted from road traffic (or from its nocturnal derivative nitrate that enhances night-time semi-volatile oxygenated OA (SV-OOA)), since NO2 concentrations increased from 19 to 42 μg m −3 from the first to the last sample.